Effects of allelochemicals from sugarcane straw on growth and physiology of weeds - Sampietro, D. A. (2007)
The phytotoxic activity of the compounds isolated was from sugarcane straw was evaluated on seedling growth of crops and weeds (Brass/ca campestris, Latium sativa, Amarantints quitensis, Bidens subalternam. and Sida riunnbifolia). Three compounds were identified : ferulic (FA), syringic (SA) and vanillic (VA) acids. VA drastically inhibited the root elongation, followed by FA and SA. These phytotoxins increased the root membrane permeability and depressed the root metabolic activity in L saliva. VA and FA inhibited the mitotic index, while, SA increased the cell division. Vanillic acid inhibited the root branching. while, FA and SA stimulated the proliferation of secondary root. As the phenolic acids were often found concentrated in top soil layers under sugarcane straw, more studies are needed to establish their participation under field conditions.